Trauma and life stories : international perspectives - Rogers, Kim Lacy; Leydesdorff, Selma; Dawson, Graham, 1956- (Routledge studies in memory and narrative, 1999)
In this volume leading academics explore the relationship between the experiences of terror and helplessness, the way in which survivors remember and the representation of these memories in the language and form of their life stories.